A Descriptive analysis of British Accents in 'Bring Me The Horizon' Interview - Ramadhani, Wiggy; Setiawan, Iwan; Suhatmady, Bibit (Edumaspul: Jurnal Pendidikan, 2024)
The British accent, spoken by individuals from the United Kingdom (UK), comes in various forms. "Bring Me The Horizon" is a renowned British band featuring British musicians who employ diverse British accents. This study aims to identify the prevalent British accent utilized by Oliver Sykes and Jordan Fish and to assess students' perceptions of the British accent spoken in the video, with the goal of facilitating their English language learning. The researcher used a descriptive qualitative research in order to gain the data.The researcher used an article from ‘Accent Bias Britain’ and was guided by a native speaker from UK in order to validate the data. The participants in this study included four students who had viewed the video. The data collection instruments comprised the video itself, transcripts of the dialogue, and an article sourced from Accent Bias Britain.. The research reveals that Oliver Sykes used General Norther English, and Jordan Fish used Multicultural London English